Software certification from process and product perspectives - Yahaya, Jamaiah; Deraman, Aziz; Baharom, Fauziah; Hamdan, Abdul Razak (Dr. Sang H. Lee, 2009)
Previous studies by other researchers in this discipline provide a set of axiom and supporting models for software assessment and quality but are not extended to a practical and well accepted model of certification. During the last five years, two preliminary works was undertaken in this research group to study issues of certification and these works are still continuing. Recently, this initial work was completed and extended. Two software certification models have been developed using requirements-designimplementation strategy to ensure that it meets the needs of a number of different interest groups in the industry.The two models focused on certifying software by development process and product quality approaches. The models have been tested by case study, which was launched collaboratively with industry in Malaysia.Further analysis has demonstrated feasibility and practicality of the models in a real environment. This paper discusses the implementation of these two models(SCfM_prod & SPAC) and their underlying results. The certification models defined in this research do not only offering a mechanism for assessment and certification, but also providing an alternative mechanism for monitoring of quality and continuous improvement of software quality throughout its life span.